PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS VII MTS MUHAMMADIYAH BAGANSIAPIAPI TAHUN PELAJARAN 2015/2016 - Gustinawati '; Yustina '; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Learning is an activity of a person in the potential uses of mind and nuraninya both in structured or not in order to gain knowledge, build up attitudes, and has certain skills. The low average value of student learning outcomes MTS Muhammadiyah Bagansiapiapi caused due to the lack of student involvement in the learning process to follow. One alternative to the workaround is to use an innovative learning models. One of the learning models that can improve student learning outcomes is a cooperative learning model of type Numbered Heads Together (NHT).The research is the research of class action aimed at improving the results of the study of biology students with the application of the cooperative learning model of type Numbered Heads Together (NHT) Class VII MTS Muhammadiyah Bagansiapiapi Lessons Year 2015/2016. This research was conducted in March-April 2016. The subject of research is the grade VII MTS Muhammadiyah Bagansiapiapi totalling 28 people which consisted of 15 students and 13 students. Parameters measured were the result of student learning that consists of absorption, ketuntasan students can study individually, the awards group and activity of students as well as teachers ' activity. The average absorbance on a cycle I was 74.28 (good) increased in cycle II becomes 80.17 (good). Ketuntasan students can study in cycle I, namely 78.57% with an average score of 74.28 and cycle II increased to 92.85% with an average score of 80.17. Group Award at the cycle I, 1 Group 4 and group super predicate predicate excellent increase in cycle II, 2 groups 3 groups and super predicate predicate excellent. Learning activities of students in cycle I, namely 77.22% (good) increased in cycle II becomes 86.82% (very good). The activity of the teacher in the cycle I and cycle II that is 100% (very good). From the results it can be concluded that the application of the cooperative learning Model of type Numbered Heads Together (NHT) can improve the results of studying biology Grade VII MTS Muhammadiyah Bagansiapiapi Lessons Year 2015/2016Key words: Cooperative Learning, Learning Outcomes, Kooperatif Type Numbered Heads Together (NHT)